Financial Statement Fraud Detection with Beneish M-Score Analysis on Soe Companies in the Mineral and Coal Industry Sector Listed on Idx - Tommy Kuncara; Ihsan (East Asian Journal of Multidisciplinary Research, 2022)
Indonesia as a country that has a bad corruption rating certainly really needs to have an overview of various frauds. Therefore, it is necessary to study fraud in Indonesia which is expected to provide a complete picture of fraud in Indonesia. This study aims to determine the detection of financial statement fraud with Beneish M-Score analysis in state-owned companies in the Mineral and Coal Industry sector that are listed on the IDX in 2018-2020 which are classified as manipulators, gray companies and non-manipulators. The data collection method is documentation with the number of samples being 3 BUMN companies in the Mineral and Coal Industry sector that are listed on the IDX in 2018-2020. The data analysis used is the Beneish Ratio Index by using five calculated Days Sales in Receivable Index (DSRI) indexes, Gross Margin Index (GMI), Asset Quality Index (AQI), Sales Growth Index (SGI), and Total Accrual To Total Assets Index (TATA). The results of the study revealed that state-owned companies in the Mineral and Coal Industry sector classified as manipulators in 2018 were not detected, 2019 1 company, 2020 was not detected. The percentage of manipulators is 11%. State-owned companies in the Mineral and Coal Industry sector classified as gray companies in 2018 1 company, 2019 not detected, 2020 not detected. The percentage of gray company is 11%. State-owned companies in the Mineral and Coal Industry sector classified as non-manipulators in 2018 2 companies, 2019 2 companies, 2020 3 companies. The percentage of gray company is 78%.